Biased policy decisions and the provision of public inputs in open economies - Michael Rauscher (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1993)
Lobbying activities bias the political decision making process. There tend to be deviations from the socially optimal solutions. This paper shows that, in an international context, this bias is not necessarily harmful from an economic-welfare point of view. It may correct externalities that occur in an international policy game when individual governments behave strategically. The strategic variable in this model is the quantity of a factor of production which is provided by the government, e.g. an infrastructure good. If both countries under consideration are large and wish to affect the remuneration of the internationally mobile factor of production, it can be seen that one country provides too much of the public input whereas the other country does not provide enough. Lobbying activities that tend to increase the supply of this input in the latter country may, therefore, lead to welfare gains for both countries involved in the jurisdictional competition provided that the resource cost of lobbying is not to high.
Keywords: 330; Interessenpolitik; Spieltheorie; Öffentliches Gut; Offene Volkswirtschaft; Theorie